Thebridestory Media Representation of Bride: Between Bridal Fiction and Consumerism - Vir Risky Kustiani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2024)
This article will explain how wedding media constructs and shapes the representation of brides in its publications. The analysis uses digital ethnographic methods with a semiotic approach to analyze Thebridestory Instagram content. Studies will be conducted to explore the representation of the bride's portrait in Thebridestory posts and what the wedding media constructs through language, symbols, and signs. Research shows that the bride portrait in Thebridestory uploads shows how bridal fiction is constructed and visualized into wedding documentation portraits. The implication of this is the celebration of a new form of feminity celebrated in the logic of consumerism. The wedding documentation published by Thebridestory narrates the idea of heteronormativiy through the celebration of women's feminity at the wedding celebration and the consumption of wedding that has become a whole. Then, the posts became a show that resulted in gazing from female audience. This representation perpetuates the patriarchal system by constructing marriage as an ideal choice for women.